2008
DOI: 10.3168/jds.2007-0679
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Feed Bunk Competition on the Feed Sorting Behavior of Close-Up Dry Cows

Abstract: The objectives of this research were to describe the feed sorting, feeding behavior, and feed intake of cows consuming a close-up ration and to determine if these behaviors are affected by competition for access to the feed bunk. Thirty-six dry Holstein cows, consuming a close-up total mixed ration diet, were assigned to 1 of 2 treatments: 1) noncompetitive (1 cow/feed bin) or 2) competitive (2 cows/feed bin). Dry matter intake, feeding behavior, and sorting behavior were monitored for each feed bin on 4 separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
4
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 19 publications
(31 reference statements)
6
61
4
5
Order By: Relevance
“…This is likely the result of cows lacking the prehensile abilities to discriminate as well against shorter ration particles (Phillips 2002). Further, in those studies that have demonstrated sorting against long particles, the long particles typically comprised a high percentage of the ration (close to 20%) due to the presence of hay or straw in the TMR Armentano 2003, 2007;Hosseinkhani et al 2008). Overall, given the use of wet forages and the low proportion of long particles in the ration, it is not surprising that no sorting of the long particles occurred.…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely the result of cows lacking the prehensile abilities to discriminate as well against shorter ration particles (Phillips 2002). Further, in those studies that have demonstrated sorting against long particles, the long particles typically comprised a high percentage of the ration (close to 20%) due to the presence of hay or straw in the TMR Armentano 2003, 2007;Hosseinkhani et al 2008). Overall, given the use of wet forages and the low proportion of long particles in the ration, it is not surprising that no sorting of the long particles occurred.…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…This may be true for individually fed cows; however, for group-fed cows, disparity in bunk access may still result in between-cow variation in nutrient intake due to sorting. With a zero-orts feeding system, it is reasonable to believe there still may be sorting throughout the day (DeVries et al 2005;Hosseinkhani et al 2008). In situations of feed bunk competition, this may result in those subordinate animals with poor feed bunk access at peak feeding periods (DeVries et al 2004) having to wait to feed at later hours in the day after the feed has already been sorted, thus increasing their risk of consuming a ration that is not designed to meet their nutritional requirements (Hosseinkhani et al 2008).…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…Differences in postweaning feeding patterns resulting from early competitive environment, as observed by Miller-Cushon et al (2014b), are consistent with differences in feeding patterns resulting from competition for access to feed in older animals: in heifers and adult cows, reducing available feeding stations or bunk space increases intake rates (Hosseinkhani et al 2008;Proudfoot et al 2009;DeVries and von Keyserlingk 2009) and competitive interactions around feed (DeVries et al 2004;Huzzey et al 2006), while decreasing meal frequencies (Hosseinkhani et al 2008;DeVries and von Keyserlingk 2009). The effect of a competitive environment on feeding patterns may have implications for long-term health of dairy cattle.…”
Section: Social Environmentmentioning
confidence: 64%
“…Whereas the degree of feed sorting has been found to vary among calves, dependent upon prior experience, the pattern of feed sorting appears to be less flexible. Post-weaning, dairy calves that sort their feed have consistently been observed selecting in favour of the higher-energy grain component (Miller-Cushon and DeVries 2011;Miller-Cushon et al 2013b, d), similar to patterns of feed sorting observed in adult cattle (Leonardi and Armentano 2003;Hosseinkhani et al 2008;Miller-Cushon and DeVries 2009). Preweaning environment has been found to have only shortlived effects on the pattern, or direction, of feed sorting post-weaning; calves exposed to either concentrate or hay prior to weaning sorted a mixed diet in favour of the familiar feed component initially after weaning, but differences in sorting patterns did not persist, with all calves beginning to sort in favour of concentrate and against hay (Miller-Cushon and DeVries 2011).…”
Section: Provision Of Solid Feedmentioning
confidence: 77%
“…Hosseinkhani et al (2008) followed the feeding behaviour of non-lactating Holstein cows (n 036) eating TMR from either their bin (one cow/bin) or a shared bin (two cows/bin). Cows that had to compete for feed access increased their feeding rate throughout the day.…”
Section: Physical Design Of the Feed Barriermentioning
confidence: 99%